Deteksi Virus Classical Swine Fever di Bali dengan RT-PCR - Wirata, I Wayan; Ayu Sri Chandra Dewi, Ida; Narendra Putra1,, I Gusti Ngurah; Oka Winaya, Ida Bagus; Kade Suardana3,, Ida Bagus; Komala Sari, Tri; Suartha, I Nyoman; Kade Mahardika, I Gusti Ngurah (Jurnal Veteriner; Vol 11 No 3 (2010))
Classical Swine Fever (CSF) virus has been confirmed for the first time in pig in Bali. The object of thisstudy was suspected CSF cases diagnosed at the diagnostic laboratory assistantship of the Faculty ofVeterinary Medicine, Udayana University, in 2007-2008. Total number of cases was 12. Case recordsincluded the signalment of case (breed, age, body weight, and the origin of respective case), clinical signs,post-mortem lesions, and histological pictures. CSF virus was confirmed using the standardized reversetranscriptase-polymerase chain reaction (RT-PCR) for CSF from European Union. One RT-PCR productwas sequenced. CSF virus was confirmed in seven out of 12 cases (58%). The cDNA sequence wasconfirmed to be specific of CSF E2 protein coding region with 98% homology to one isolate from China thatwas available in GeneBank. Further works are recommended to elucidate the sensitivity of RT-PCR, toclarify some differential diagnose, and to find out the genetic variation of CSF virus in Bali.Key words: classical swine fever virus, Bali, RT-PCR
Keywords: classical swine fever virus, Bali, RT-PCR